2011
DOI: 10.1371/journal.pone.0026915
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms in Fibromyalgia Are Better Associated to Lipid Peroxidation Levels in Blood Mononuclear Cells Rather than in Plasma

Abstract: BackgroundWe examined lipid peroxidation (LPO) in blood mononuclear cells (BMCs) and plasma, as a marker of oxidative damage, and its association to clinical symptoms in Fibromyalgia (FM) patients.MethodsWe conducted a case–control and correlational study comparing 65 patients and 45 healthy controls. Clinical parameters were evaluated using the Fibromyalgia Impact Questionnaire (FIQ), visual analogues scales (VAS), and the Beck Depression Inventory (BDI). Oxidative stress was determined by measuring LPO in BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…This result is consistent with findings from illnesses that have low vitality and fatigue as core symptoms. Reports indicate that chronic fatigue syndrome and fibromyalgia are accompanied by higher oxidized low density lipoproteins and elevated protein carbonyl levels in the blood [10, 33-36]. In addition, elevated levels of 8-hydroxy-deoxyguanosine, a marker of oxidative damage to DNA, had been found in the urine of chronic fatigue patients [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings from illnesses that have low vitality and fatigue as core symptoms. Reports indicate that chronic fatigue syndrome and fibromyalgia are accompanied by higher oxidized low density lipoproteins and elevated protein carbonyl levels in the blood [10, 33-36]. In addition, elevated levels of 8-hydroxy-deoxyguanosine, a marker of oxidative damage to DNA, had been found in the urine of chronic fatigue patients [37].…”
Section: Discussionmentioning
confidence: 99%
“…For example, changes in psychiatric disorders are not only found in the brain, but also in peripheral markers, such as cytokines [8, 9]. Moreover, PBMCs have been shown to be a suitable cell model for mitochondrial dysfunction and oxidative stress in biomarker discovery for Alzheimer's disease, fibromyalgia and chronic fatigue syndrome [10-12]. …”
Section: Introductionmentioning
confidence: 99%
“…A line of studies by Cordero and his colleagues has focused on MDF in FM, reporting on decreased ΔΨ and CoQ10 levels, along with excess mt ∙ O 2 − production and excess mitophagy [291293]. …”
Section: Miscellaneous Pathologiesmentioning
confidence: 99%
“…FMS pain is not only associated with symptoms affecting life quality, but their presence could also imply a higher risk of chronic diseases. Interestingly, it has been observed that FMS patients have more oxidative damage than controls, which could be translated into a higher cardiovascular risk [26].…”
Section: Fibromyalgia Syndromementioning
confidence: 99%